The Aerodynamic Design of a Compliant Morphing Flap for Next-Generation Hybrid Electric Regional Aircraft - Francesco Antonio D’Aniello; Pietro Catalano; Domenico Quagliarella; Mauro Minervino (Engineering Proceedings, 2025)
The focus of this paper is on some of the activities performed by CIRA under the framework of the HERWINGT project (Hybrid Electric Regional Wing Integration Novel Wing Technologies) supported by the Clean Aviation Joint Undertaking and funded by the European Union. The aim of the project is to design an innovative wing suitable for future hybrid electric regional aircraft (HER) that will contribute to the overall target of reducing fuel burn, CO2, and other GHG emissions by improving aerodynamic efficiency and reducing weight. The aerodynamic design of a high-lift system of wings in the form of a compliant morphing flap is presented in this paper. A morphing flap was designed through CIRA’s in-house-developed evolutionary optimization software employing the SU2 open source RANS flow solver. The required performances can be achieved by a configuration equipped with both flap and droop noses, with flow control applied to mitigate the separation occurring over the rear upper region of the wing section. This has become particularly important for landing performances. Analyses were conducted for a 2D wing section. Requirements for the flow control system in terms of mass flow and maximum extension of the separated region were formulated.